Are Changes in Corticomotor Excitability Associated with Improved Arm Functional Performance Following a Tailored Strength Training Intervention in Chronic Stroke Survivors? - Stephania Palimeris; Yekta Ansari; Anthony Remaud; François Tremblay; Hélène Corriveau; Marie-Hélène Boudrias; Marie-Hélène Milot (Brain Sciences, 2025)
Background/Objectives: We showed that a tailored strengthening intervention based on the size of motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) in the affected hemisphere resulted in an improved affected arm function, regardless of stroke severity. Also, adding anodal transcranial direct stimulation (atDCS) during training did not alter the results as participants receiving real or sham stimulation showed similar gains. The goal of this study was to report on the changes in basic measures of corticomotor excitability in response to the intervention and to determine whether these changes were influenced by tDCS and correlated with those measured in arm function. Methods: The TMS measures consisted of the resting motor threshold (rMT), MEP amplitude at rest, and the silent period (SP) duration. Clinical outcomes included the Box and Block test (BBT) and grip strength (GS). Results: Post-intervention, regardless of atDCS (p > 0.62), no significant change in corticomotor excitability was noted (p > 0.15), as well as no association between the changes in TMS measures and arm function gains (p > 0.06). Conclusions: As observed for clinical measures, atDCS did not influence corticomotor excitability. The absence of an increase in the excitability of the affected hemisphere and important associations between changes in corticomotor excitability and clinical gains suggest that factors other than brain plasticity could mediate gains in arm function. Further investigations are required regarding the role of tDCS in stroke rehabilitation.